Формулювання елементів організаційно-розпорядчих документів з захисту ВзОД та ІзОД - Малахова, А. А. (ХНУРЕ, 2023)
The relevance of the topic of standardization of the design of business papers simplifies and speeds up the preparation and perception of the text of the document makes it objective and reliable. The general and most characteristic feature of documents is that they are a source or carrier of information, are widely used in everyday activities, contribute to the improvement of the internal organization of any institution. One of some of the tasks facing civil servants is it is necessary to leam how to correctly prepare business documents, constantly increase their language culture. Currently in organizations of state and local authorities the government of state disagreement in the preparation of certain business papers